2022
DOI: 10.3390/genes13071151
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Analyses of DNA Methylation and Gene Expression of Rainbow Trout Muscle under Variable Ploidy and Muscle Atrophy Conditions

Abstract: Rainbow trout, Oncorhynchus mykiss, is an important cool, freshwater aquaculture species used as a model for biological research. However, its genome reference has not been annotated for epigenetic markers affecting various biological processes, including muscle growth/atrophy. Increased energetic demands during gonadogenesis/reproduction provoke muscle atrophy in rainbow trout. We described DNA methylation and its associated gene expression in atrophying muscle by comparing gravid, diploid females to sterile,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 83 publications
0
1
0
Order By: Relevance
“…Rainbow trout is one of the most important fish, but genome annotation is still incomplete compared to the model species such as zebrafish ( 1 ). For aquaculture breeding, a well-annotated reference genome sequence is essential for genomic-based animal selection ( 2 ). The human ENCODE project showed that the major category of the active genome transcription comprises noncoding RNAs ( 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…Rainbow trout is one of the most important fish, but genome annotation is still incomplete compared to the model species such as zebrafish ( 1 ). For aquaculture breeding, a well-annotated reference genome sequence is essential for genomic-based animal selection ( 2 ). The human ENCODE project showed that the major category of the active genome transcription comprises noncoding RNAs ( 3 ).…”
Section: Introductionmentioning
confidence: 99%